English Language Teaching in Spain: Do Textbooks Comply with the Official Methodological Regulations? A Sample Analysis - Criado, Raquel; Sánchez, Aquilino (International Journal of English Studies, 2009)
The goal of this paper is to verify up to what point ELT textbooks used in Spanish educational settings comply with the official regulations prescribed, which fully advocate the Communicative Language Teaching Method (CLT). For that purpose, seven representative coursebooks of different educational levels and modalities in Spain – secondary, upper secondary, teenager and adult textbooks – were selected to be analysed. A full unit randomly selected from each coursebook was examined through the parameters of the communicative potential of the activities – measured on a scale from 0 to 10 – and the communicative nature of the methodological strategies implemented – measured on a dichotomous scale (yes/no). Global results per educational levels point to the prevailing communicative nature of all the materials, which was shown to be above 50%. The remaining non-communicative block was covered by activities focused on the formal features of language (grammar and vocabulary). This resulting degree of dissociation between official regulations and what is really found in teaching materials may be positive, since the learning of languages is complex and results from the intervention of multiple factors and learning styles, as is evidenced by the professional experience of teachers from different backgrounds and beliefs.